(untitled) (Journal of Engineering, 2024)
For projects such as airports and road paving, an appropriate foundation must be developed in Sabkha soil, which requires a trustworthy assessment of soil-bearing capacity. When heavy traffic is expected to result in substantial wheel loads throughout pavement construction and maintenance, the plate load test helps solve these issues with subgrade and sub-base layer design. This work aims to investigate and assess the geotechnical behavior regarding soil strata from one area in southern Iraq: Sabkha. Conversely, a comparison is made between subgrade response modulus and soil-bearing capacity determined by field plate load tests and traditional laboratory investigations. The data demonstrated that the values related to Ks in the consolidation test rose as a ratio of pre-consolidation pressure of 45% and dramatically dropped with an increase in applied stress that is vertically applied below pre-consolidation stress. Furthermore, PLT data demonstrated that when pressure was applied, the modulus of the subgrade reaction did not follow a regular pattern. At the beginning of the loaded stage, after the pre-consolidation stress, Ks values at testing points 2 and 3 were high. After that, Ks abruptly decreased, particularly when the applied pressure surpassed the pre-consolidation stress before being constant again. A detailed discussion is given on the effects of stress distribution and test conditions on the elasticity stress curve’s shape and the subgrade reaction modulus.